Prevalence and health outcomes of combustible cigarettes and noncombustible nicotine or tobacco products: a nationwide cross-sectional study in South Korea - Tae Hyeon Kim; Yeona Jo; Jaewon Kim; Krishna Prasad Acharya; Hanseul Cho; Ho Geol Woo; Jiyoung Hwang; Dong Keon Yon (Preventive Medicine Reports)
Objective: Limited evidence exists on type of tobacco use changes and differential health outcomes following the introduction of non-combustible nicotine or tobacco products (NNTPs). Therefore, this study aimed to evaluate the characteristics, trends, and health outcomes of exclusive combustible cigarette users and dual users of combustible cigarette and NNTP. Methods: This study analyzed data from the Korea National Health and Nutrition Examination Survey from 2013 to 2021 (n = 18,763). Individuals aged ≥19 years were included in the study. Type of tobacco use were categorized into exclusive combustible cigarette users or dual users. Health outcomes assessed included stroke, angina pectoris, hypertension, dyslipidemia, type 2 diabetes, rheumatoid arthritis, allergic rhinitis, atopic dermatitis, and depression. Prevalence trends were estimated using weighted complex survey analysis, with results presented as weighted prevalence and 95 % confidence intervals (CIs). Health outcomes by type of tobacco use were evaluated using multivariable logistic regression, providing adjusted odds ratios (aORs) with 95 % CIs. Results: Exclusive combustible cigarette user showed a decreasing trend, while dual exhibited a showed increase. This shift from exclusive combustible cigarette user to dual user was particularly evident among younger, highly educated, and higher-income individuals. Compared to exclusive combustible cigarette users, dual users exhibited significantly associations with depression (aOR, 1.50 [95 % CI, 1.19–1.89]), atopic dermatitis (1.39 [1.10–1.74]), and allergic rhinitis (1.30 [1.14–1.49]). Conclusions: The prevalence of dual use is increasing and is associated with a higher risk of depression, atopic dermatitis, and allergic rhinitis.